FROM TRADITION TO TREND: A CRITICAL REVIEW FROM THE PERSPECTIVE OF EDUCATIONAL SOCIOLOGY ON THE FACTORS DRIVING PARENTS IN LOMBOK TO CHOOSE TAHFIZ SCHOOLS - Palahuddin (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2026)
In recent years, there has been an interesting phenomenon in which urban communities, including those in Lombok, West Nusa Tenggara, have shown a high level of interest in Quran-based educational institutions, particularly the tahfiz education model. This study aims to analyze the factors driving the increasing preference among parents in Lombok for Quran-based tahfiz education and to examine this phenomenon from an educational sociology perspective. The study employs a qualitative approach using library research within the theoretical framework of the sociology of education. Data were analyzed using an interactive data analysis method comprising the three-stage model of Miles et al.: data reduction, data presentation, and drawing conclusions. The results indicate that parents’ preference for tahfiz schools is influenced by several key factors: religiosity as a value foundation, the cultural habitus of the Sasak community, concerns about moral degradation due to modernity, and rational considerations that integrate worldly and otherworldly dimensions. In the context of holistic Islamic education, this phenomenon must be critically addressed, as the dominance of tahfiz education has the potential to reduce the meaning of education to a symbol of piety, reinforce the dichotomy of knowledge, and encourage the commodification of religious education. Therefore, there is a need to develop an integrative model of tahfiz education that emphasizes not only memorization but also comprehension, character building, and intellectual development (science and technology).